Collection of microorganisms of ICG SB RAS as a genetic resource for biotechnology - A. V. Bryanskaya; Y. E. Uvarova; A. S. Rozanov; N. M. Slynko; V. N. Shlyakhtun; K. V. Starostin; E. A. Demidov; E. V. Lazareva; O. P. Taran; S. E. Peltek (Вавиловский журнал генетики и селекции)
Genetic knowledge of microorganisms plays a critical role in the creation of new biotechnologies, since the effectiveness of any biotechnology is determined by the particular qualities of the structurally functional organization of molecular-genetic systems and their components used for the production of targeted products. Collections of microbial cultures play a decisive role in mobilizing biological resources and make it possible to form a solid base for genetic, molecular biological and biotechnological research. The aim of this work was to assess the key molecular-genetic and phenotypic characteristics of strains of the collection of microorganisms created in the “FRC Institute of Cytology and Genetics of the Siberian Branch of the Russian Academy of Sciences” as a genetic resource for biotechnology. Thirty strains of microorganisms of the collection were isolated by employees of the FRC ICG SB RAS from extreme natural ecosystems, the key molecular-genetic and phenotypic characteristics were described using modern methods of molecular biology and mass-spectrometry. DNA isolation and the sequencing of 16S rRNA gene sequences were performed. The strains of the collection were characterized by morphological, physiological, moleculargenetic and mass-spectrometric characteristics. The particular qualities of growing of strains on different substrates have been established, the study of cell morphology has been carried out. The physiological characteristics of the strains of the collection have been established: the attitude to oxygen, the type of nutrition, the range of temperature and pH, the attitude to NaCl and others. Different resistance of strains to antibiotics has been established. The creation of personal mass spectra of protein profiles of the studied strains of the collection was carried out. The resulting DNA sequences of the strains are deposited in the GenBank. The chemotaxonomic characteristics of strains have been determined. The biotechnological properties of the strains were assessed, the amount of metabolites (ethanol, lactic and acetic acids) in the culture liquid was determined. The value of the collection of microorganisms of the FRC ICG SB RAS as a genetic resource for biotechnology and bioengineering is determined not only by the species diversity of its strains, but also by a wide range of their area isolation and by the depth of their characterization using the widest arsenal of both classical and modern methods (including methods of genomics, proteomics, transcriptomics and bioinformatics).